Human laminopathies: nuclei gone genetically awry - Capell, Brian C.; Collins, Francis S. (Nature reviews. Genetics, 2006)
Key Points Over 180 mutations have been reported in the genes of the nuclear lamina, in particular LMNA , causing diseases termed 'laminopathies.' The number of identified laminopathies has steadily increased in recent years, currently including 13 known conditions. LMNA encodes lamin A and lamin C, which are important components of the nuclear lamina, a dynamic protein meshwork that lies inside the inner nuclear membrane. The nuclear lamina has a vital role, not only in maintenance of nuclear shape and structure, but also in transcriptional regulation, nuclear pore positioning and function, and heterochromatin organization. The laminopathies show many overlapping phenotypes, which could represent a spectrum of disease rather than a set of completely distinct clinical entities. These phenotypes include skeletal and cardiac myopathies, lipodystrophies, neuropathies, skeletal dysplasias and characteristics of premature ageing. As research unveils increasingly complex roles of the lamina in a diverse array of nuclear processes, evidence indicates that laminopathy phenotypes might result from a complex combination of cellular defects. These include fragile, mechanically unstable nuclei, loss of peripheral heterochromatin and other epigenetic changes, altered transcription, disrupted DNA replication, deficient DNA repair and impaired differentiation. Hope for successful therapeutic strategies for the laminopathies has been mainly provided by promising work in Hutchinson–Gilford progeria syndrome, for which studies have focused on the use of farnesyltransferase inhibitors, RNAi and modified oligonucleotides. Continued use of the array of mouse models of laminopathies that are currently available, the generation of new models, and further advances in cellular imaging promise to further correlate the numerous genotype–phenotype relationships among the laminopathies. Future research also promises a deeper exploration into the potential links between the phenotypes of these rare diseases and the much more common conditions of atherosclerosis and ageing. Intense investigation of the laminopathies has revised the traditional structural view of the nuclear lamina, highlighting crucial roles in processes including gene regulation and differentiation. This research has also led to a range of promising therapies for these rare diseases. Few genes have generated as much recent interest as LMNA , LMNB1 and LMNB2 , which encode the components of the nuclear lamina. Over 180 mutations in these genes are associated with at least 13 known diseases — the laminopathies. In particular, the study of LMNA , its products and the phenotypes that result from its mutation have provided important insights into subjects ranging from transcriptional regulation, the cell biology of the nuclear lamina and mechanisms of ageing. Recent studies have begun the difficult task of correlating the genotypes of laminopathies with their phenotypes, and potential therapeutic strategies using existing drugs, modified oligonucleotides and RNAi are showing real promise for the treatment of these diseases.